Pathogenicity of Trichobilharzia spp. for Vertebrates - Lichtenbergová, Lucie; Horák, Petr (Journal of parasitology research, 2012)
Bird schistosomes, besides being responsible for bird schistosomiasis, are known as causative agents of cercarial dermatitis. Cercarial dermatitis develops after repeated contact with cercariae, mainly of the genus Trichobilharzia, and was described as a type I, immediate hypersensitivity response, followed by a late phase reaction. The immune response is Th2 polarized. Primary infection leads to an inflammatory reaction that is insufficient to eliminate the schistosomes and schistosomula may continue its migration through the body of avian as well as mammalian hosts. However, reinfections of experimental mice revealed an immune reaction leading to destruction of the majority of schistosomula in the skin. Infection with the nasal schistosome Trichobilharzia regenti probably represents a higher health risk than infections with visceral schistosomes. After the skin penetration by the cercariae, parasites migrate via the peripheral nerves, spinal cord to the brain, and terminate their life cycle in the nasal mucosa of waterfowl where they lay eggs. T. regenti can also get over skin barrier and migrate to CNS of experimental mice. During heavy infections, neuroinfections of both birds and mammals lead to the development of a cellular immune response and axonal damage in the vicinity of the schistosomulum. Such infections are manifest by neuromotor disorders.